Pulmonary hypertension in adults with congenital heart defects (ACHDs) in light of the 2022 ESC PAH guidelines—part II: supportive therapy, special situations (pregnancy, contraception, non-cardiac surgery), targeted pharmacotherapy, organ transplantation, special management (shunt lesion, left ventricular disease, univentricular hearts), interventions, intensive care, ACHD follow-up, future perspective - Kaemmerer, Harald; Diller, Gerhard Paul; Dähnert, Ingo; Achenbach, Stephan; Eichstaedt, Christina A.; Eicken, Andreas; Freiberger, Annika; Freilinger, Sebastian; Geiger, Ralf; Gorenflo, Matthias; Grünig, Ekkehard; Hager, Alfred; et al. (Cardiovascular Diagnosis and Therapy, 2024)
The number of adults with congenital heart defects (ACHDs) is steadily increasing and is about 360,000 in Germany. Congenital heart defect (CHD) is often associated with pulmonary hypertension (PH), which sometimes develops early in untreated CHD. Despite timely treatment of CHD, PH not infrequently persists, redevelops in older age, and is associated with significant morbidity and mortality. The revised European Society of Cardiology (ESC)/European Respiratory Society (ERS) 2022 guidelines for the diagnosis and treatment of PH represent a significant contribution to the optimized care of those affected. However, the topic of “adults with congenital heart defects” is treated only relatively superficially in this context. After the first part commenting on a broad range of topics like definition, epidemiology, classification, diagnostics, genetics, risk stratification and follow-up, and gender aspects, the second part focuses on supportive therapy, special situations (pregnancy, contraception, non-cardiac surgery), targeted pharmacotherapy, organ transplantation, special management [shunt lesion, left ventricular (LV) disease, univentricular hearts], interventions, intensive care, ACHD follow-up, and future perspective. In the present article, therefore, this topic is commented on from the perspective of congenital cardiology. By examining these aspects in detail, this article aims to fill the gaps in the existing guidelines and provide a more thorough understanding from the perspective of congenital cardiology.
CRIS-Team Scopus Importer:2024-11-08
Keywords: congenital heart defect (CHD); Eisenmenger syndrome (ES); Pulmonary arterial hypertension (PAH)